2022
DOI: 10.1039/d2ob00025c
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in asymmetric synergistic catalysis – the judicious combination of selected chiral aminocatalysts with achiral metal catalysts

Abstract: In this review we survey the most recent synergistic applications of a chiral organocatalyst with an achiral metal to perform stereoselective transformations of synthetic utility (since 2016). The transformations are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…116,117 In addition, integrating the photochemical activity of chiral organocatalytic intermediates within metal-mediated catalytic cycles may also enable unconventional mechanisms for stereocontrolled bond formation. 118 6.3. Late-Stage Functionalization.…”
Section: Stereochemistry and Isomerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…116,117 In addition, integrating the photochemical activity of chiral organocatalytic intermediates within metal-mediated catalytic cycles may also enable unconventional mechanisms for stereocontrolled bond formation. 118 6.3. Late-Stage Functionalization.…”
Section: Stereochemistry and Isomerizationmentioning
confidence: 99%
“…New research findings have also shown that by using light to excite chiral organocatalytic intermediates, novel catalytic functions can be activated, thus enabling the synthesis of chiral molecules that would otherwise be challenging to obtain using conventional ground-state reactivity. Therefore, the photochemistry of organocatalytic intermediates can open up new synthetic possibilities, expanding the scope of organocatalysis to encompass radical chemistry and excited-state reactivity. , In addition, integrating the photochemical activity of chiral organocatalytic intermediates within metal-mediated catalytic cycles may also enable unconventional mechanisms for stereocontrolled bond formation …”
Section: Hit-to-lead and Lead Optimizationmentioning
confidence: 99%
“…The integration of organocatalysis and transition-metal catalysis is increasingly recognized as a potent strategy 5a f h 7 for creating vicinal stereogenic centers via nucleophilic allylic substitution reactions. Organocatalysts, 7,8 including chiral phase-transfer reagents, amines, aldehydes, N -heterocyclic carbenes (NHCs), and Lewis bases, are commonly employed to activate the pre-nucleophiles, and transition-metal catalysts, notably palladium and iridium, are utilized to activate allylic electrophiles.…”
Section: Construction Of Vicinal Stereogenic Centers By Organo and Me...mentioning
confidence: 99%
“…4c,d To utilize these less reactive carbonyl compounds in catalytic asymmetric allylic substitution, they often require stoichiometric pre-activation into the corresponding metal enolates, silyl enol ethers, or enamines. 4c Chiral amine and transition-metal dual catalysis 5a c h has been instrumental in broadening the range of enolate nucleophiles in catalytic asymmetric allylic allylation processes.…”
Section: Construction Of Vicinal Stereogenic Centers By Organo and Me...mentioning
confidence: 99%
“…Synergistic metal–organo catalysis has flourished into a highly significant and useful strategy in chemical synthesis, where the complementary modes of substrate activation would bring about novel types of transformations or improve the efficiency and chemo-, regio-, and stereoselectivities of known reactions . In this context, the combination of a transition metal and primary or secondary amine catalysts has attracted considerable attention from synthetic chemists, who merged enamine catalysis with several modes of electrophile activation with transition-metal catalysts for carbonyl α-functionalizations, such as α-allylation and -alkylation reactions .…”
mentioning
confidence: 99%